Heroic Self-discovery of the Shepherd in Paulo Coelho’s The Alchemist - Regmi, Dipendra Raj (The Outlook: Journal of English Studies, 2020)
This paper examines the heroic self-discovery of a common shepherd in Paulo Coelho’s The Alchemist (1988) through the concept of popular culture. Santiago, the protagonist, abandons his home and family in teenage for a mysterious hidden treasure. What are the reasons that make him to undertake an adventurous journey from the known to the unknown land? So this paper draws on ideas from Marshall W. Fishwick and Joseph Campbell to respond the shepherd’s journey in order to substantiate his expedition as an adventure of the hero. Santiago’s journey of self- discovery can be analyzed in the theoretical frame of the hero journey and the quest of myth. Therefore, Santiago’s journey from Andalusia to Africa in search of a hidden treasure is uncommon because he begins his journey in a response to an exotic recurring dream where a child summons him to the Pyramids of Egypt. This is the reason why his journey differs from the celebrities, artists, politicians, and mythical heroes.